2019
DOI: 10.4103/jfmpc.jfmpc_443_18
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors of gastroesophageal reflux disease among Shaqra University students, Saudi Arabia

Abstract: Introduction:Gastroesophageal reflux disease (GERD) is one of the most common chronic gastrointestinal disorders in adults, it develops when the stomach contents reflux and rise up into the esophagus as a result from lower esophageal sphincter dysfunction. Stomach acid that touches the lining of the esophagus causes symptoms and complications. The classical symptoms of GERD include heartburn, usually after eating, chest pain, and regurgitation.Aim:To measure the prevalence of gastroesophageal reflux disease an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

10
33
2
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(64 citation statements)
references
References 27 publications
(36 reference statements)
10
33
2
2
Order By: Relevance
“…Even though the presented percentage of males and females in our study was not representative of the population, it followed a similarity when compared to major studies with no significance found in terms of gender [8,9,18]. However, Alrashed et al [11] indicated that the male population was at higher risk for developing GERD and supported their results through a report in India that revealed similar findings [13].…”
Section: Discussionsupporting
confidence: 63%
See 2 more Smart Citations
“…Even though the presented percentage of males and females in our study was not representative of the population, it followed a similarity when compared to major studies with no significance found in terms of gender [8,9,18]. However, Alrashed et al [11] indicated that the male population was at higher risk for developing GERD and supported their results through a report in India that revealed similar findings [13].…”
Section: Discussionsupporting
confidence: 63%
“…After summation of the scores, the patients who scored an 8 or more were considered positive for GERD. GerdQ sensitivity and specificity for GERD diagnosis was 65% and 71%, respectively [10,11].…”
Section: Data Collection and Sampling Techniquementioning
confidence: 97%
See 1 more Smart Citation
“…9 The incidence of GERD was more in the BMI group of 26 to 28 kg/m 2 (n ¼ 10) which is in consonance with previous studies. [10][11][12] The prominent clinical symptoms were heartburn, regurgitation, water brash and nausea. As per GerdQ, 28 cases were moderate and two cases were severe.…”
Section: Discussionmentioning
confidence: 99%
“…This has its equivalent of load: chronic stress and a period of complete relaxation. Such a distribution of time is one of the factors in the formation of the disease: during the exams "there is no time to get sick", and after they end -a long period of rest without attention to the health [17].…”
Section: Introductionmentioning
confidence: 99%